2021
DOI: 10.15184/aqy.2020.169
|View full text |Cite
|
Sign up to set email alerts
|

Material cosmopolitanism: the entrepot of Harlaa as an Islamic gateway to eastern Ethiopia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
(42 reference statements)
0
29
0
Order By: Relevance
“…Such changes in orientation, along with the use of stone slabs to cover some of the grave pits, precisely mirror the practices recorded in the Muslim cemetery at Harlaa (see Insoll et al 2021). This perhaps indicates that Muslim-Christian interaction was occurring at Lalibela, although the presence of ceramics in some graves (Derat et al 2021)-presumably as grave goods that are not usually found in Islamic contexts (Insoll 1999: 172)-suggests greater complexity.…”
Section: Timothy Insollmentioning
confidence: 66%
See 4 more Smart Citations
“…Such changes in orientation, along with the use of stone slabs to cover some of the grave pits, precisely mirror the practices recorded in the Muslim cemetery at Harlaa (see Insoll et al 2021). This perhaps indicates that Muslim-Christian interaction was occurring at Lalibela, although the presence of ceramics in some graves (Derat et al 2021)-presumably as grave goods that are not usually found in Islamic contexts (Insoll 1999: 172)-suggests greater complexity.…”
Section: Timothy Insollmentioning
confidence: 66%
“…Subsequently, excavations in Harar have revealed a range of settlement and mosque sites dating between the late fifteenth and nineteenth centuries (Insoll 2017;Insoll & Zekaria 2019). Much work, however, remains to be done, and ongoing excavations in Harlaa and Tigray (Insoll et al 2021;Loiseau et al 2021) attest the potential of archaeology both for reconstructing medieval Islamic life and the complexity and cosmopolitanism that defined it.…”
Section: Islam and Muslim Politiesmentioning
confidence: 99%
See 3 more Smart Citations